Visibilidade e Cultura - Leite, Maria Angela Faggin Pereira (Paisagem e Ambiente, 1999)
Reality changes and transformations seeking a desirable future, can be seen as processes that consider landscape forms as a means of com m unicating a kind of social consciousness, w hich gives meaning and relevance to territory occupation. The possibility of perceiving and understanding what is beeing represented in the changes of social order. This article refers to these processes and its developments/influences in landscape design